Mobile Banking Service Quality and Customer Retention: A Moderated Mediation Model of Customer Perceived Value and Perceived Corporate Image - Daniel Kipkirui Langat; Ronald Bonuke; Yusuf Kibet (SEISENSE Journal of Management, 2021)
Purpose- This study examined the moderating effect of perceived corporate image on the indirect relationship between mobile banking service quality and customer retention via customer perceived value in the Kenyan banking industry